The relationship between macroeconomic variable and exchange rate: A case in Japan / Siti Nor Fatimah Abdul Jalil - Abdul Jalil, Siti Nor Fatimah (2018)
This study to analyse the relationship the changes in Japanese yen and macroeconomic in underlying fundamental and allow to explain the movement in Japanese yen and US dollar. This study to analyze the relationship the changes in Japanese yen and macroeconomic in underlying fundamental and allow to explain the movement in Japanese yen and US dollar. There are several analysis which is start with Correlation, Descriptive and Multiple Regression Model. Besides that, there are a few test such as Autocorrelation, Multicollinearity and Heteroskedasticity. The sample that had been tested from Eikon, Bank of Japan and World Bank. The data provided from 1983 to 2016. The expected was all variable have significant relationship. However, the real result shown that 2 significant relationship which were export and crude oil while 3 significant relationship which were inflation, interest rate and Gross Domestic Product. This relationship had been supported by previous authors.